Ultrasound-Enhanced Supercritical CO2 Extraction of Masson Pine Wood Essential Oil - Yu, Xian-Chun; Sun, De-Lin; Li, Xiang-Su (Asian Journal of Chemistry, 2011)
Ultrasound-enhanced supercritical CO2 was used to extract the essential oil of masson pine. The extraction technology was optimized through orthogonal experiments. The results showed that a good outcome can be achieved with an extraction pressure of 18 MPa, a temperature of 60 ºC, a time of 90 min, a CO2 flow rate of 12 kg h-1, an ultrasonic power of 250 W and an ultrasonic frequency of 22 KHz. Using these parameters, the average yield of essential oil was 88.12 %. GC-MS analysis showed that the ingredient with the highest content of 44.42 % was longifolene in the essential oil of masson pine wood, followed by a-pinene and caryophyllene, with contents of 28.17 and 6.03 %, respectively.